Two on the Field: Critical Sitings - Javier/Xavier Navarro (Oz, 1990)
Memory. An intricate concept when stripped of its apparent banality. Memory: remembrance, recollection, personal or collective, chronological or random, surreal or sensual? More questions than I will furnish answers to.